Microbiota-Based Therapeutics for COVID-19 and Sequelae - Oliveira, Gislane Lelis Vilela De (Springer Nature, 2024)
The COVID-19 pandemic has considerable worldwide impact, resulting in widespread fatalities and diverse clinical symptoms. Many patients experience long COVID, characterized by persistent symptoms beyond the acute phase. It can be categorized as subacute (4–12 weeks post-COVID) or chronic (beyond 12 weeks). Patients frequently report ongoing symptoms such as dyspnea, cough, anosmia/ageusia, fatigue, chest pain, anxiety, depression, and sleep disorders post-discharge. Both acute COVID-19 and post COVID-19 condition are influenced by the immune system, with the intestinal microbiota playing a pivotal role. The two-way communication between the respiratory and gut mucosa, known as the gut–lung axis, impacts immune responses to SARS-CoV-2 and post-COVID syndromes. Targeting the microbiota to restore a healthy balance offers potential therapeutic benefits. Probiotic supplementation has shown promise in rebalancing the intestinal microbiota and modulating immune function. In conclusion, the COVID-19 pandemic has far-reaching consequences, including post COVID-19 condition. Understanding the microbiota’s role in immune responses and exploring probiotic interventions can help mitigate the long-term effects of acute COVID-19.